(untitled) (SciComm Report, 2025)
In the context of the triple planetary crisis (pollution, biodiversity loss, and climate change), a negative impact on people’s mental health is observed. New concepts emerge in global media and within the field of psychology to represent the negative feelings accompanying the global ecological crises, both present and future, such as ’eco-anxiety’ and ’climate anxiety.’ Through this review, a theoretical and conceptual differentiation of both concepts is made, from a historical and problematizing perspective on the terminology, to contextualize the current challenges in Latin America, within the framework of emerging research in Chile, and to identify opportunities for the development of research lines and thematic areas that could be relevant in addressing increasingly complex challenges.